2020
DOI: 10.3390/pharmaceutics12121188
|View full text |Cite
|
Sign up to set email alerts
|

Hydrogels as Drug Delivery Systems: A Review of Current Characterization and Evaluation Techniques

Abstract: Owing to their tunable properties, controllable degradation, and ability to protect labile drugs, hydrogels are increasingly investigated as local drug delivery systems. However, a lack of standardized methodologies used to characterize and evaluate drug release poses significant difficulties when comparing findings from different investigations, preventing an accurate assessment of systems. Here, we review the commonly used analytical techniques for drug detection and quantification from hydrogel delivery sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
165
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 272 publications
(166 citation statements)
references
References 224 publications
(442 reference statements)
1
165
0
Order By: Relevance
“…The pH is acidic in the stomach (pH 2) and becomes basic in the intestine (pH 5 to 8) [45]. Blood, on the other hand, has a pH value of 7.4 [46]. The microenvironmental pH can also vary and change during pathogenesis and disease progression, and, for example, become acidic in an immediate tumor environment [47,48], during the wound healing process [49], or in the case of infection [46].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pH is acidic in the stomach (pH 2) and becomes basic in the intestine (pH 5 to 8) [45]. Blood, on the other hand, has a pH value of 7.4 [46]. The microenvironmental pH can also vary and change during pathogenesis and disease progression, and, for example, become acidic in an immediate tumor environment [47,48], during the wound healing process [49], or in the case of infection [46].…”
Section: Introductionmentioning
confidence: 99%
“…In the intestinal tract, it varies from close to 0 M in the stomach to 0.4 M in the intestine, in relation to a fed or fasted state [50][51][52][53][54]. The general physiological ionic strength is 150 mM [46].…”
Section: Introductionmentioning
confidence: 99%
“…In order to be defined a drug delivery system, a formulation should retain the entrapped compound(s), promoting a gradual/controlled/sustained release as a function of time [76]. In this regard, among different factors, it has been reported that the network size of a hydrogel plays a critical role in the choice of the administration route as well as in the modulation of the release kinetic of the entrapped compound [74,77].…”
Section: Natural Polymer-based Hydrogels In Anti-cancer Therapymentioning
confidence: 99%
“…Hydrogels are soft materials that retain high levels of water that are widely used for their adsorption and delivery properties in areas such as drug [ 1 ] or protein [ 2 ] release, tissue engineering [ 3 , 4 ], and wound healing [ 3 , 5 ]. They are typically composed of a three-dimensional network that traditionally arises from chains of polymers [ 6 ], polysaccharides [ 7 ], proteins [ 8 ], or other macromolecules.…”
Section: Introductionmentioning
confidence: 99%